Vehicle wiper blades
By controlling the elastic modulus and coefficient of variation of the tapered part of the vehicle wiper blade, the problems of insufficient wipeability and uneven contact in the prior art are solved, and efficient removal and stable wiping effect of strong adhesion dirt is achieved.
Patent Information
- Application Number
- CN202180058814.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-28
- Filing Date
- 2021-07-30
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-07-30
AI Technical Summary
When using existing vehicle wiper blades to treat dirt with strong adhesion such as dust and oil films, the wipeability is insufficient, which can easily lead to uneven contact and vibration, affecting the operator's field of vision and wiping effect.
By controlling the elastic modulus of the conical part of the wiper blade and its coefficient of variation, it is ensured to be within a specific range (15MPa~470MPa, coefficient of variation below 17.6%) to achieve stable and efficient wipe.
The stable removal of dust and oil film attached to the members to be cleaned is achieved, and the wipeability and durability of the wiper blade is improved, and the uneven contact and trembling phenomenon is reduced.
Smart Images

Figure CN116057099B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a vehicle wiper blade for wiping a surface of a member to be cleaned. Background Art
[0002] For example, automobiles, trains, ships, and airplanes are provided with cleaning members for the purpose of wiping off water drops or dirt attached to glass surfaces such as windshields and rear windshields and thereby ensuring the operator's field of vision.
[0003] Among such cleaning members, a wiper blade having a wiper blade rubber provided on a portion in contact with a glass surface is well known. Water drops and the like attached to the glass surface can be wiped off by close-contact motion of the wiper blade rubber on the glass surface. From the viewpoint of ensuring a good field of vision for an operator, it is desirable that the wiper blade is excellent in wiping properties and can fully wipe off water drops and dirt and the like from the glass surface.
[0004] PTL 1 discloses that the wiping quality during a desired service life can be improved by forming a coating film containing carbon fibers on the surface of a wiper blade rubber.
[0005] Citation List
[0006] Patent Literature
[0007] [PTL1] Japanese Patent Publication No. 2011-518713 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In recent years, in order to ensure a good field of vision, it has become increasingly common to apply water repellent treatment or wax coating to glass surfaces. As a result, local wiping properties are improved, but uneven abutment and chattering may occur in some cases. The abnormal sound caused by uneven abutment may make the operator feel uncomfortable, and the chattering itself may lead to a decrease in wiping properties.
[0010] It has been shown that the wiper blade disclosed in PTL 1 has fine abutment unevenness depending on the dispersion state and coating state of the added carbon fiber. When the wiper blade for a vehicle is used in such a state, abutment unevenness may occur in relation to the wiping performance of water droplets.
[0011] Meanwhile, conventional wiper blades such as represented by PTL 1 may not be able to easily wipe off strongly adherent dirt such as dust and oil film such as particles and asphalt contained in vehicle exhaust gas from the glass surface when the dirt adheres to the glass surface.
[0012] One aspect of the present disclosure is directed to providing a vehicle wiper blade that can stably exert excellent wiping performance and also makes it possible to scrape off strongly adherent dirt such as dust and oil film adhered to a member to be cleaned.
[0013] Solutions for solving problems
[0014] The present inventors have found that in order to improve the wiping performance of a vehicle wiper blade against strongly adherent dirt such as dust and oil film, it is effective to control the elastic modulus and its coefficient of variation of a specific portion of the tapered portion that contacts the member to be cleaned within a specific range.
[0015] According to one aspect of the present disclosure, there is provided a vehicle wiper blade for a wiper device for a vehicle windshield, comprising:
[0016] a scraper blade support; and
[0017] a lip pivotably connected to the blade support via a neck;
[0018] The lip has a tapered portion in which the width of the lip gradually decreases from a side close to the blade support portion toward a direction farthest from the blade support portion in a cross section along a direction perpendicular to the length direction of the wiper blade;
[0019] Lips have
[0020] A first tapered surface and a second tapered surface constituting a tapered portion; and
[0021] a front end surface, the front end surface, together with the first tapered surface and the second tapered surface, forming a first edge and a second edge on a side of the lip portion that is farthest from the blade support portion;
[0022] Assume that a first line segment is drawn on the first conical surface, parallel to the first edge and at a distance of 10 μm from the first edge;
[0023] Define the length of the first line segment as L1;
[0024] Points on the first line segment that are (1 / 8)L1, (1 / 2)L1, and (7 / 8)L1 away from one end are defined as P0, P1, and P2, respectively; and
[0025] When the elastic modulus of the first tapered surface is measured at 70,000 points at a pitch of 0.1 μm in each of three rectangular observation areas, each of which has a point P0, P1, and P2 as a center of gravity and has a side of 70 μm in length parallel to the first line segment and a side of 10 μm in length perpendicularly intersecting the first line segment, using a scanning probe microscope,
[0026] The average value of the 210,000 elastic modulus values obtained is 15 MPa to 470 MPa, and the coefficient of variation of the elastic modulus is 17.6% or less; and
[0027] Assume that a second line segment is drawn on the second conical surface, parallel to the second edge and at a distance of 10 μm from the second edge;
[0028] Define the length of the second line segment as L2;
[0029] Points on the second line segment that are (1 / 8)L2, (1 / 2)L2, and (7 / 8)L2 away from one end are defined as P3, P4, and P5, respectively; and
[0030] When the elastic modulus of the second tapered surface is measured at 70,000 points at a pitch of 0.1 μm in each of three rectangular observation areas, each of which has points P3, P4, and P5 as a center of gravity and has a side of 70 μm in length parallel to the second line segment and a side of 10 μm in length perpendicularly intersecting the second line segment, using a scanning probe microscope,
[0031] The average value of 210,000 elastic modulus values obtained was 15 MPa to 470 MPa, and the coefficient of variation of the elastic modulus was 17.6% or less.
[0032] Effects of the Invention
[0033] One aspect of the present disclosure allows for providing a vehicle wiper blade that can stably exert excellent wiping performance and also makes it possible to scrape off strongly adherent dirt such as dust and oil film adhered to a member to be cleaned. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] [ Figure 1 ]An example of a schematic diagram of a wiper blade.
[0035] [ Figure 2 ] Figure 2 (a) and Figure 2 (b) is an explanatory diagram showing the state of the wiper blade during cleaning.
[0036] [ Figure 3 ]Enlarged view near the first edge.
[0037] [ Figure 4 ]Enlarged view near the first line segment.
[0038] [ Figure 5 ]An enlarged view of the observation area 12 with P0 as the center.
[0039] [ Figure 6 ] Figure 6(a) and Figure 6 (b) is a schematic diagram of the vicinity of the contact portion between the wiper blade and the member to be cleaned. DETAILED DESCRIPTION
[0040] In the present disclosure, unless otherwise specified, the description of "XX or more and YY or "XX to YY" indicating a numerical range means a numerical range including the lower limit and the upper limit as endpoints. When a numerical range is described in sections, the upper and lower limits of each numerical range can be arbitrarily combined.
[0041] <Construction of vehicle wiper blade>
[0042] A vehicle wiper blade (hereinafter also simply referred to as a wiper blade) according to one aspect of the present disclosure is used for, for example, vehicles such as automobiles, transportation equipment such as airplanes and ships, and industrial machinery such as construction machinery.
[0043] like Figure 1 As shown in FIG. 1 , a vehicle wiper blade of a wiper device for a vehicle windshield has a blade support portion 1 and a lip portion 3 swingably connected to the blade support portion via a neck portion 2. The wiper blade is formed to have substantially the same cross-sectional shape along the length direction.
[0044] The lip portion 3 has a tapered portion 4 in which the width of the cross section of the lip portion 3 in a direction perpendicular to the longitudinal direction gradually decreases from a side close to the blade supporting portion 1 in a direction away from the blade supporting portion 1 .
[0045] The wiper blade cleans the surface of a member to be cleaned, such as a glass surface, by bringing a part of the tapered portion into contact with the surface of the member to be cleaned.
[0046] For example, in a cross section perpendicular to the length direction of the wiper blade, the width of the neck portion 2 may be narrower than the blade support portion 1 and the lip portion 3 .
[0047] Therefore, if Figure 2 As shown in FIG. 1 , the lip 3 is inclined in the wiping direction so that a part of the tapered portion abuts against the member to be cleaned.
[0048] Figure 2 of Figure 2 (a) and Figure 2 (b) is an explanatory diagram showing the state of the wiper blade during the cleaning process.
[0049] exist Figure 2In (a), the lip portion 3 of the wiper blade has: a first tapered surface 5 constituting the tapered portion 4 abutting against the member to be cleaned 10 and a second tapered surface 6 on the opposite side of the first tapered surface 5; and a front end surface 7, wherein the front end surface 7, together with the first tapered surface 5 and the second tapered surface 6, constitutes a first edge 8 and a second edge 9 on the side of the lip portion 3 farthest from the blade support portion 1 (for the first edge, the second edge and the front end surface, see Figure 1 and Figure 3 ).
[0050] exist Figure 2 In (b), the lip portion 3 of the wiper blade has a second tapered surface 6 constituting the tapered portion 4 abutting against the member to be cleaned 10 and a first tapered surface 5 on the opposite side of the second tapered surface 6; and a front end surface 7, wherein the front end surface 7, together with the first tapered surface 5 and the second tapered surface 6, constitutes a first edge 8 and a second edge 9 on the side of the lip portion 3 farthest from the blade support portion 1 (for the first edge, the second edge and the front end surface, see Figure 1 and Figure 3 ). Arrow R indicates the cleaning direction of the wiper blade. Figure 2 The sweep direction of arrow R in (a) is switched to the Figure 2 As a result of cleaning in the direction of arrow R in (b), the surface in contact with the member to be cleaned is switched from the first tapered surface 5 to the second tapered surface 6 .
[0051] Figure 3 It is an enlarged view near the first edge 8.
[0052] like Figure 3 As shown in FIG. 1 , at the front end of the wiper blade abutting against the member to be cleaned, a first line segment 11 is drawn on the first tapered surface 5 parallel to the first edge 8 at a distance of 10 μm from the first edge 8. Here, L1 represents the length of the first line segment.
[0053] Figure 4 is an enlarged view near the first line segment. Figure 4 As shown in FIG. 1 , P0, P1, and P2 respectively represent points on the first line segment 11 that are (1 / 8) L1, (1 / 2) L1, and (7 / 8) L1 away from one end.
[0054] Herein, three rectangular observation areas 12 are set on the first conical surface 5, each of which has a side with a length of 70 μm parallel to the first line segment and a side with a length of 10 μm perpendicularly intersecting the first line segment 11, and each of which has a point P0, P1 and P2 on the first line segment as its center of gravity.
[0055] Figure 5 An enlarged view of the vicinity of the observation area 12 with P0 as the center is shown.
[0056] Using a scanning probe microscope (hereinafter referred to as SPM), Figure 5 Similarly, in each of the three observation areas including both P1 and P2, P0 in FIG. 1 , the elastic modulus of the first tapered surface was measured at 70,000 points at a pitch (interval) of 0.1 μm.
[0057] The average value of a total of 210,000 elastic modulus values obtained was 15 MPa to 470 MPa, and the coefficient of variation of the elastic modulus was 17.6% or less.
[0058] Similar to the measurement of the first tapered surface, at the front end of the wiper blade abutting against the member to be cleaned, a second line segment is drawn on the second tapered surface 6 parallel to the second edge 9 and at a distance of 10 μm from the second edge 9. Here, L2 represents the length of the second line segment.
[0059] Furthermore, P3, P4, and P5 represent points on the second line segment that are (1 / 8)L2, (1 / 2)L2, and (7 / 8)L2 away from the one end, respectively.
[0060] Herein, three rectangular observation areas are set on the second conical surface 6, each of which has a side with a length of 70 μm parallel to the second line segment and a side with a length of 10 μm perpendicularly intersecting the second line segment, and each of which has points P3, P4 and P5 on the second line segment as its center of gravity.
[0061] Using SPM, the elastic modulus of the second tapered surface was measured at 70,000 points at a pitch (interval) of 0.1 μm for each of the three observation areas.
[0062] The average value of a total of 210,000 elastic modulus values obtained was 15 MPa to 470 MPa, and the coefficient of variation of the elastic modulus was 17.6% or less.
[0063] The behavior of the reciprocating wiper blade during cleaning was observed in detail. As a result, it was found that the wiper blade relative to the cleaned component was in contact with the cleaned component on the first conical surface and the second conical surface, in an area including positions approximately 10 μm from the first edge and the second edge. The wiper blade according to the present disclosure can prevent the occurrence of wiping residue and wiping unevenness at the wiping portion of the cleaned component because the average value of the elastic modulus along the length direction of each area that can constitute the above-mentioned contact portion with the cleaned component and the coefficient of variation of the elastic modulus meet predetermined regulations.
[0064] In a wiper blade according to one aspect of the present disclosure, the average value of the elastic modulus values measured at predetermined positions 10 μm away from the first edge and the second edge on the first conical surface and the second conical surface that can constitute a contact portion abutting against the cleaned member and along the length direction of the area near the 10 μm position is 15MPa to 470MPa, and the coefficient of variation of the elastic modulus is 17.6% or less. The average value of the elastic modulus value is preferably greater than 32MPa and less than 62MPa. The coefficient of variation of the elastic modulus is preferably less than 6.0%. The coefficient of variation of the elastic modulus is preferably as small as possible, so the lower limit is not particularly limited, but is, for example, greater than 0.1%.
[0065] When the average value of the elastic modulus value is within the above range, a portion of the tapered surface can be brought into contact with the member to be cleaned with a narrow width in the length direction of the wiper blade during cleaning. That is, the contact portion can be brought into approximate line contact, wherein the pressing force is concentrated on the contact portion, and it is possible to reliably scrape off the attached matter from the member to be cleaned, rather than simply wiping or smearing it off. As a result, an extremely high wiping performance can be exerted compared to a conventional wiper blade.
[0066] The feature that the coefficient of variation of the elastic modulus is 17.6% or less means in this article that the elastic modulus at the contact portion of the tapered surface is more uniform or more homogeneous along the length direction of the tapered surface. As a result, the wiper blade can be brought into contact with the component to be cleaned with a narrow width along the length direction of the blade. As a result, this enables uniform tracking and abutment with the component to be cleaned, while suppressing the occurrence of vibrations and the like during cleaning and eliminating disturbances of the cleaning surface along the length direction of the wiper blade. Therefore, for highly adhesive contaminants such as dust and oil film attached to the component to be cleaned, excellent wiping properties can be stably exhibited in the entire area of the wiper blade along the length direction without wiping residues and uneven wiping.
[0067] The coefficient of variation of the elastic modulus was calculated according to the following formula (1).
[0068] Formula (1): Coefficient of variation (%) = standard deviation / average value of elastic modulus value × 100
[0069] For example, when a wiper blade is pressed against a component to be cleaned according to automobile measurement standards, in the case of a conventional vehicle wiper blade, near the contact portion, the abutment angle is about 25°, the width of the contact portion with the component to be cleaned (nip width) is 20 to 30 μm, and the maximum contact pressure is 1.5 MPa.
[0070] In contrast, the wiper blade of the present disclosure obtained measurements including an abutment angle of about 55°, a nip width of 5-6 μm, and a contact pressure of 6.0 MPa.
[0071] Figure 6 A schematic diagram showing the vicinity of the contact portion between the wiper blade and the member to be cleaned.
[0072] like Figure 6 As shown in (a), the conventional wiper blade contacts the cleaned component with a tapered surface in a planar contact state (surface contact). Figure 6 As shown in (b), it is found that the wiper blade of the present disclosure contacts the edge of the member to be cleaned with its tapered surface in a state of nearly line contact.
[0073] The material constituting the tapered portion is not particularly limited as long as it is a material that can form a contact portion with the member to be cleaned and that satisfies the above regulations for the average value of the elastic modulus values near the positions 10 μm from the first edge and the second edge of the first tapered surface and the coefficient of variation of the elastic modulus. Specifically, for example, the tapered portion preferably includes polyurethane that exhibits excellent mechanical properties and easily satisfies the above regulations on the average value and coefficient of variation of the elastic modulus.
[0074] In addition, the above-mentioned polyurethane is preferably a polyurethane elastomer. The polyurethane elastomer is mainly obtained from raw materials such as polyols, chain extenders, polyisocyanates, catalysts and other additives. The above-mentioned polyurethane elastomer is a block copolymer consisting of a hard segment and a soft segment. The hard segment is usually composed of a chain extender such as polyisocyanates and a short-chain diol. The soft segment is usually composed of a polyisocyanate and a long-chain polyol such as a polyester polyol, a polyether polyol or a polycarbonate polyol.
[0075] For example, in order to achieve the average value of the elastic modulus value and adjust the coefficient of variation of the elastic modulus, the characteristics of the block copolymer composed of the hard segment and the soft segment can be utilized.
[0076] Conventional polyurethanes have hard segments in which the portions resulting from the aggregation of the interactions of carbamate bonds in turn further aggregate with each other. The aggregated portions of the carbamate bond portions have relatively large hard segments resulting from further aggregation. As a result, studies conducted by the inventors revealed that the wiper blades produced using such polyurethanes do not satisfy at least one of the average value of the elastic modulus value and the coefficient of variation of the elastic modulus according to the present disclosure. That is, conventional polyurethanes have relatively large hard segments, and therefore it is difficult to make the coefficient of variation of the elastic modulus at 210,000 sites less than 17.6% when using a scanning probe microscope as in the present disclosure. It is believed that in the case of polyurethanes with a small amount of hard segments themselves, further aggregation of the aggregated portions of the carbamate bonds can be suppressed, and the coefficient of variation can be kept small. However, in this case, it is difficult to set the average value of the elastic modulus value to more than 15MPa.
[0077] The tapered portion satisfying the physical properties according to the present disclosure can be formed, for example, by using a polyurethane in which a hard segment is finely and uniformly dispersed. Such a polyurethane is described below.
[0078] Specifically, by using a polyurethane raw material in the form of a diisocyanate or a trifunctional or higher polyfunctional isocyanate and a diol or a trifunctional or higher polyfunctional alcohol within an appropriate concentration range, a polyurethane is obtained in which hard segments are finely and uniformly dispersed and hard segment aggregation is suppressed.
[0079] Specifically, for example, at least one of an alcohol including a trifunctional or higher polyfunctional alcohol and an isocyanate compound including a trifunctional or higher polyfunctional isocyanate is preferably used as the polyurethane raw material.
[0080] It is also preferable to use an isocyanate compound containing at least one alcohol selected from diols and trifunctional or higher polyfunctional alcohols and containing trifunctional or higher polyfunctional isocyanate as the polyurethane raw material.
[0081] It is also preferred to use, as polyurethane raw materials, alcohols including trifunctional or higher polyfunctional alcohols and isocyanate compounds including diisocyanates and trifunctional or higher polyfunctional isocyanates.
[0082] It is particularly preferable to use trifunctional or higher polyfunctional isocyanates and trifunctional or higher polyfunctional alcohols as polyurethane raw materials.
[0083] The polyurethane obtained as the reaction product of trifunctional or higher polyfunctional isocyanate and trifunctional or higher polyfunctional alcohol exhibits suppressed molecular orientation due to steric hindrance, so that hard segment aggregation is more reliably suppressed. As a result, the polyurethane is a suitable polyurethane in achieving the elastic modulus and coefficient of variation according to the present disclosure.
[0084] In addition, in the case where the soft segment portion has, for example, a linear alkylene structure, the crystallinity is improved by stacking the soft segments. As a result, the hard segments are not easily dispersed. Therefore, in this article, the introduction of an alkylene structure having a side chain portion into the soft segment portion is effective in suppressing the aggregation of the hard segments. Specifically, for example, the introduction of partial structures such as those represented by the following structural formulas (i) to (iv) into the soft segment portion between two urethane bonds is effective for miniaturizing the hard segments.
[0085] -CH2-CH(CH3)-CH2-CH2-O-(i)
[0086] -CH2-CH2-CH(CH3)-CH2-O-(ii)
[0087] -CH2-CH(CH3)-O-(iii)
[0088] -CH(CH3)-CH2-O-(iv)
[0089] Substantially the same structure of formula (i) and (ii) is obtained by ring-opening polymerization of 3-methyltetrahydrofuran. Substantially the same structure of formula (iii) and (iv) is obtained by ring-opening polymerization of 1,2-propylene oxide. Herein, polyurethane resins having these structures between two adjacent urethane bonds can be obtained by reacting a polyether polyol or polyester polyol having these structures with an isocyanate. In the case of using difunctional alcohols (diols) and difunctional isocyanates (diisocyanates) as polyurethane raw materials, it is generally difficult to achieve micro-dispersion of the hard segment. However, by introducing the above-mentioned partial structure into the soft segment portion, the hard segment can be micro-dispersed even when diols and diisocyanates are used. As a result, a polyurethane for producing a wiper blade that meets the parameters according to the present disclosure can be obtained.
[0090] In addition to the above-mentioned method of introducing a side chain into the soft segment portion, the method for inhibiting the crystallization from the stacking of the soft segment and preventing the aggregation of the hard segment also includes, for example, a method involving the use of two or more alcohols with different carbon numbers of the linear portion as the alcohol in the polyurethane raw material. In the polyurethane obtained by using two or more alcohols with different carbon numbers of the linear portion, even when the soft segment portion has a linear alkylene structure, the crystallization from the stacking of the soft segment can be suppressed due to the different carbon numbers. Considering the different carbon numbers of the soft segment portion, the aggregation of the urethane bond portion is thus suppressed, and as a result, the hard segment is prevented from aggregating. Therefore, in the case of using diisocyanate and a diol having a linear alkylene structure in the molecule as a polyurethane raw material, by using a plurality of diols with different carbon numbers of the linear alkylene structure as the above diols in this article, the hard segment can also be micronized. As a result, a polyurethane for producing a wiper blade that meets the parameters according to the present disclosure can be obtained. Examples of a variety of diols include, for example, the combined use of polybutylene adipate polyester polyol and polyhexane adipate polyester polyol.
[0091] Examples of the above-mentioned alcohols include the following.
[0092] Polyester polyols such as polyethylene adipate polyester polyol, polybutylene adipate polyester polyol, polyhexane adipate polyester polyol, (polyethylene / polypropylene) adipate polyester polyol, (polyethylene / polybutylene) adipate polyester polyol, and (polyethylene / polyneopentene) adipate polyester polyol; polycaprolactone-based polyols obtained by ring-opening polymerization of caprolactone; polyether polyols such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol; and polycarbonate diol. The foregoing substances may be used alone or in combination of two or more.
[0093] As described above, it is preferred to use two or more polyols having different numbers of carbon atoms in the linear part (alkylene chain) because, in this case, a polyurethane in which soft segment crystallization is suppressed and hard segment aggregation is suppressed is obtained. In this case, it is preferred to use, for example, at least two selected from the group consisting of polyester polyols such as polyethylene adipate polyester polyol, polybutylene adipate polyester polyol, polyhexane adipate polyester polyol, (polyethylene / polypropylene) adipate polyester polyol, (polyethylene / polybutylene) adipate polyester polyol, and (polyethylene / polyneopentylene) adipate polyester polyol.
[0094] As the chain extender, a diol or a trifunctional or higher-functional alcohol that can extend the chain of the polyurethane elastomer can be used.
[0095] Examples of the diols include the following.
[0096] Ethylene glycol (EG), diethylene glycol (DEG), propylene glycol (PG), dipropylene glycol (DPG), 1,4-butanediol (1,4-BD), 1,6-hexanediol (1,6-HD), 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, xylylene glycol (p-phenylenediol), and triethylene glycol. The above substances can be used alone or in combination of two or more.
[0097] Examples of trifunctional or higher polyfunctional alcohols include trimethylolpropane (TMP), glycerol, pentaerythritol, and sorbitol. The above substances may be used alone or in combination of two or more.
[0098] One of the methods for increasing the elastic modulus of polyurethane elastomers may involve, for example, introducing a cross-linked structure. A preferred method for introducing cross-linking involves using a trifunctional or higher polyfunctional alcohol as the above-mentioned chain extender. Herein, a branched structure is introduced into polyurethane by using a trifunctional or higher polyfunctional alcohol so as to suppress polyurethane crystallization and further suppress hard segment aggregation. Preferably, from the viewpoint of suppressing excessive hardness rise caused by excessive cross-linking degree of polyurethane, a trifunctional alcohol is used as a polyfunctional alcohol. Among them, triols are preferred, because triols have a methylene skeleton adjacent to a hydroxyl group, a soft cross-linked structure can be produced in the molecular structure, and the effect of further suppressing hard segment crystallinity is caused. Examples of such triols include, for example, trimethylolpropane (TMP) and glycerol.
[0099] Examples of the above-mentioned isocyanate compound include the following.
[0100] 4,4'-diphenylmethane diisocyanate (4,4'-MDI), polymeric MDI, 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), xylene diisocyanate (XDI), 1,5-naphthalene diisocyanate (1,5-NDI), para-phenylene diisocyanate (PPDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), 4,4'-dicyclohexylmethane diisocyanate (hydrogenated MDI), tetramethylxylene diisocyanate (TMXDI), carbodiimide-modified MDI, triphenylmethane-4,4',4"-triisocyanate (TTI) and tris(phenylisocyanate)phosphorothioate (TPTI).
[0101] Among them, 4,4'-MDI is preferred, because the two isocyanate groups of 4,4'-MDI have equal reactivity, and the compound obtains high mechanical properties. Preferably, a trifunctional or higher polyfunctional isocyanate is used. Herein, the use of a trifunctional or higher polyfunctional isocyanate allows the branched structure to be introduced into polyurethane, and is effective in further suppressing the aggregation of hard segments. In addition, a denser cross-linked structure can be introduced into polyurethane, so that the abutment of the elastic part and the member to be cleaned can be made more stable. As a result, it becomes possible to effectively suppress the wiping residue and uneven wiping of the member to be cleaned.
[0102] Examples of trifunctional or higher polyfunctional isocyanates include at least one selected from the group consisting of triphenylmethane-4,4',4"-triisocyanate (TTI), tris(phenylisocyanate) phosphorothioate (TPTI) and polymeric MDI. Among them, tris(phenylisocyanate) phosphorothioate (TPTI) and polymeric MDI can be more suitably used. These isocyanates have a methylene group or an ether group between multiple NCO groups, so that the distance between multiple urethane bonds can be appropriately maintained. Therefore, these isocyanates are advantageous in suppressing the aggregation of hard segments.
[0103] Polymeric MDI is represented by the following chemical formula (1) and chemical formula (1)'. In chemical formula (1)', n is preferably 1 or more and 4 or less. Chemical formula (1) is a case where n is 1 in chemical formula (1)'.
[0104]
[0105] Preferably, the tapered portion according to the present disclosure exhibits the following physical properties when the tapered portion includes polyurethane which is a reaction product of a raw material composition including an isocyanate compound containing a diisocyanate and a trifunctional or higher polyfunctional isocyanate and an alcohol including a trifunctional or higher polyfunctional alcohol.
[0106] Specifically, it is assumed that each line segment is drawn on the first and second tapered surfaces of the tapered portion, parallel to the first and second edges, and at a distance of 0.5 mm from the first and second edges. L' is used as the length of each line segment, and P0', P1', and P2' represent points on the line segment that are 1 / 8L', 1 / 2L', and 7 / 8L' away from one end, respectively.
[0107] Using a direct sample introduction type mass spectrometer that heats and vaporizes the sample in an ionization chamber and ionizes the sample molecules, each sample collected at the above-mentioned P0', P1' and P2' on the first conical surface and the second conical surface is heated to 1000°C at a heating rate of 10°C / s. Herein, M1 represents the detection amount of all ions obtained as a result, and M2 represents the integrated intensity of the peak in the extracted ion temperature spectrum corresponding to the range of m / z values derived from trifunctional or higher polyfunctional isocyanates. Preferably, M2 / M1 on the first conical surface and / or the second conical surface is 0.0010 to 0.0150, and particularly preferably M2 / M1 is 0.0030 to 0.0150.
[0108] Taking M3 as the integrated intensity of the peak in the extracted ion thermogram corresponding to the range of m / z values derived from diisocyanates, M3 / M1 on the first conical surface and / or the second conical surface is preferably 0.0200 to 0.1100, and particularly preferably 0.0380 to 0.0760. Since M2 / M1 and M3 / M1 are within the above range, an appropriate amount of low-crystalline structure derived from a trifunctional or higher polyfunctional isocyanate is introduced into the polyurethane; as a result, the aggregation of the hard segments can be suppressed, and the hard segments can be made finer and more uniformly dispersed. In addition, the excessive development of the cross-linked structure in the polyurethane can be suppressed, and the average value of the elastic modulus can be easily adjusted to a range of more than 15 MPa and less than 470 MPa.
[0109] Preferably, M2 / M3 is set within a range of 0.0130 or more and 0.3000 or less. Herein, M2 / M3 is a parameter representing the ratio of the structural part derived from diisocyanate to the structural part derived from trifunctional or higher polyfunctional isocyanate in the structure derived from isocyanate in the polyurethane, and thus by setting M2 / M3 within the above range, a polyurethane in which an excessive increase in elastic modulus can be restricted and hard segment aggregation can be further suppressed can be obtained.
[0110] In the case where the polyurethane is a polyurethane produced using the polymerized MDI represented by the above chemical formula (1)' as a trifunctional or higher polyfunctional isocyanate, M2 can be set to the sum of the integrated intensities of the peaks corresponding to the m / z values in the range of 380.5 to 381.5 originating from n=1, the m / z values in the range of 511.5 to 512.5 originating from n=2, the m / z values in the range of 642.5 to 643.5 originating from n=3 and the m / z values in the range of 773.5 to 774.5 originating from n=4 in the structure represented by the chemical formula (1)' in the extracted ion thermogram obtained by the above mass spectrometry analysis.
[0111] When the polyurethane is a polyurethane using 4,4′-MDI represented by chemical formula (2) as one of the raw materials used as diisocyanate, M3 can be set to the integrated intensity of the peak corresponding to the m / z value in the range of 249.5 to 250.5 derived from the structure represented by chemical formula (2).
[0112]
[0113] Preferably, the tapered portion of the wiper blade according to one aspect of the present disclosure has the following physical properties when the tapered portion contains a polyurethane as a reaction product of the following raw material composition: the raw material composition contains an isocyanate compound containing a trifunctional or higher polyfunctional isocyanate and an alcohol containing a trifunctional or higher polyfunctional alcohol. Specifically, in each line segment drawn on the first and second tapered surfaces of the tapered portion, parallel to the first and second edges, at a distance of 0.5 mm from the first and second edges, and with L' as the length of each line segment, P0', P1' and P2' respectively represent points on the line segment that are 1 / 8L', 1 / 2L' and 7 / 8L' from one end side. The samples sampled at the above-mentioned P0', P1' and P2' on the first and second tapered surfaces are measured by pyrolysis GC / MS (gas chromatography and mass spectrometry). The concentration of the component derived from trifunctional or higher polyfunctional alcohol in the polyurethane is preferably 0.04 mmol / g to 0.39 mmol / g, more preferably 0.14 mmol / g to 0.39 mmol / g, and still more preferably 0.22 mmol / g to 0.39 mmol / g.
[0114] When the concentration of the component derived from trifunctional or higher polyfunctional alcohol is 0.04 mmol / g or more, the aggregation of hard segments in the polyurethane can be more reliably suppressed. In addition, since the concentration of the component derived from trifunctional or higher polyfunctional alcohol is 0.39 mmol / g or less, the excessive development of the cross-linked structure in the polyurethane can be suppressed, and the elastic modulus can be prevented from becoming too high. Therefore, the conical portion having the above-mentioned physical properties can more easily meet the above-mentioned regulations on the average value of the elastic modulus value (15 to 470 MPa) and the coefficient of variation of the elastic modulus (less than 17.6%). The concentration of trifunctional or higher polyfunctional alcohol in the polyurethane is calculated according to the following formula (2).
[0115] Formula (2): Concentration of trifunctional or higher polyfunctional alcohol (mmol / g) =
[0116] [Amount of trifunctional or higher polyfunctional alcohol (g) / molecular weight of trifunctional or higher polyfunctional alcohol × 1000] / [mass of polyurethane (g)]
[0117] The polyurethane raw material may contain a catalyst for promoting the reaction of the isocyanate compound with the alcohol. A commonly used catalyst for curing polyurethane elastomers may be used as a catalyst; examples thereof include tertiary amine catalysts, specifically the amines exemplified below. Amino alcohols such as dimethylethanolamine, N,N,N'-trimethylaminopropylethanolamine and N,N'-dimethylhexanolamine; trialkylamines such as triethylamine; tetraalkyldiamines such as N,N,N'N'-tetramethyl-1,3-butanediamine; and triethylenediamine, piperazine compounds and triazine compounds. Alkali metal organic acid salts such as potassium acetate and potassium octoate may also be used. Metal catalysts commonly used for polyurethaneization such as dibutyltin dilaurate may also be used. The above substances may be used alone or in combination of two or more.
[0118] The raw material constituting the tapered portion of the wiper blade may contain pigments, plasticizers, water repellents, antioxidants, ultraviolet absorbers, light stabilizers, etc. as needed within a range that does not affect the elastic modulus and its coefficient of variation of the tapered portion.
[0119] <Surface treatment>
[0120] The tapered portion of the wiper blade may be subjected to surface treatment. Preferred surface treatment methods in the present disclosure include, for example, (i) a method comprising the step of irradiating the object to be treated with ultraviolet rays, and (ii) a method comprising the step of coating the object to be treated with a curing region forming material and curing the material.
[0121] (i) The conditions for irradiation with ultraviolet rays are not particularly limited. The wavelength of the ultraviolet rays may be 400 nm or less, but is preferably 200 nm or more. If the wavelength of the ultraviolet rays is 200 nm or more, the elastic modulus can be effectively increased. Preferably, the wavelength of the maximum luminescence peak of the light emitted by the light source is 200 nm or more and 400 nm or less. Particularly preferably, the wavelength of the maximum luminescence peak is around 254 nm, for example, within the range of 254±1 nm. This is because ultraviolet rays within the above-mentioned wavelength region or at the above-mentioned wavelength can effectively generate active oxygen that modifies the surface of the tapered portion of the wiper blade. In the case where there are multiple ultraviolet luminescence peaks, preferably one of the peaks is present around 254 nm.
[0122] The intensity of light emitted from the light source is not particularly limited, and a value measured using, for example, a spectroradiometer (trade name: USR-40V / D, manufactured by Ushio Inc.) or an ultraviolet integrated light meter (trade name: UIT-150-A, UVD-S254, VUV-S172, or VUV-S365, manufactured by Ushio Inc.) may be employed. The integrated light amount of ultraviolet rays irradiated to the tapered portion of the wiper blade in the surface treatment process may be appropriately selected depending on the surface treatment effect to be obtained. Irradiation with light from the light source may be performed, for example, depending on the irradiation time, the output of the light source, and the distance from the light source, and, for example, it may be specified to obtain, for example, 10,000 mJ / cm 2 The desired accumulated light amount.
[0123] The cumulative amount of ultraviolet light irradiated to the tapered portion of the wiper blade can be calculated as follows.
[0124] UV cumulative light intensity (mJ / cm 2 ) = UV intensity (mW / cm 2 )×irradiation time (sec)
[0125] For example, a high pressure mercury lamp or a low pressure mercury lamp can be suitably used as a light source for emitting ultraviolet rays. These light sources are preferred because they can stably emit ultraviolet rays having a suitable wavelength with less attenuation caused by the irradiation distance and allow uniform irradiation of the entire surface.
[0126] (ii) The conditions for applying the solidification region forming material and solidifying it are not particularly limited. The solidification region in the tapered portion can be formed by applying and solidifying the solidification region forming material. The process effectively increases the elastic modulus of the solidified portion by applying the solidification region forming material. Preferably, the solidification region is formed on at least the first tapered surface and the second tapered surface of the lip portion that abut against the cleaned member.
[0127] The solidified region forming material can be used after being diluted with a diluting solvent as needed, and can be applied by means of known means such as dipping, spraying, dispenser coating, brushing or roller coating. After applying the solidified region forming material, a heat treatment can be performed. Preferably, the solidified region forming material is infiltrated into the polyurethane contained in the elastic member. Herein, the infiltration is promoted by increasing the concentration of the solidified region forming material and reducing the viscosity of the solidified region forming material, and as a result, the solidified region forming material can be heated and infiltrated without dilution. The degree of solidification can be adjusted, for example, according to the time of infiltration or impregnation, the heat treatment temperature after infiltration or impregnation, the heat treatment time and / or the subsequent placement time.
[0128] The temperature of the solidified region forming material can be set to a range of about 60°C to 90°C. The impregnation or immersion time cannot be generalized, but the range is preferably about 10 seconds to 180 seconds. The heat treatment can be performed after the solidified region forming material is applied to the solidified region. As a result of the heat treatment, the viscosity of the solidified region forming material present on the surface of the polyurethane becomes lower; in turn, this allows the penetration and diffusion of the material into the interior of the polyurethane to be promoted.
[0129] The heating method is not particularly limited and may be a method involving passing through a heating furnace or a method involving blowing hot air. The heating furnace includes, for example, a radiation type heating furnace and a circulating wind type heating furnace, and the device for forming hot air includes a hot air blower and a far infrared heater.
[0130] By setting the heating conditions to high temperature and / or long time, the curing area can be made wider. In the preferred heating conditions, the surface temperature of the treated surface is set to, for example, within the range of 90° C. to 110° C. Preferably, the heating time is set to, for example, within the range of 10 minutes to 60 minutes.
[0131] In addition, the amount of residual isocyanate during the polyurethane formation tends to gradually decrease over time after the formation. Therefore, although not limited to this, the cured region can be formed immediately after the polyurethane is formed. For example, the cured region can be formed within 3 hours after the polyurethane is formed. The amount of residual isocyanate can also be adjusted based on the mixing ratio of the composition used when the polyurethane is formed.
[0132] The cured region forming material is not particularly limited as long as it cures polyurethane or forms a cured region on the surface of polyurethane.
[0133] Examples of the material include isocyanate compounds and acrylic compounds. The cured region forming material may be used after being diluted with a solvent or the like. The solvent used for dilution is not particularly limited as long as it dissolves the material used, and examples thereof include toluene, xylene, butyl acetate, methyl isobutyl ketone, and methyl ethyl ketone.
[0134] When the constituent material of the tapered portion of the wiper blade is polyurethane, in consideration of compatibility and impregnation with the tapered portion material, an isocyanate compound, which is a constituent material of polyurethane, is more preferably used as the material for forming the cured region. Herein, as the isocyanate compound, an isocyanate compound having one or more isocyanate groups in the molecule can be used.
[0135] Examples of the isocyanate compound having one isocyanate group in the molecule include aliphatic monoisocyanates such as octadecyl isocyanate (ODI) and aromatic monoisocyanates such as phenyl isocyanate (PHI).
[0136] As the isocyanate compound having two isocyanate groups in the molecule, compounds commonly used in the production of polyurethane resins can be used; examples of such compounds include the following: 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), 4,4'-diphenylmethane diisocyanate (MDI), metaphenylene diisocyanate (MPDI), tetramethylene diisocyanate (TMDI), hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI).
[0137] For example, as the isocyanate compound having three or more isocyanate groups in the molecule, 4,4',4"-triphenylmethane triisocyanate, 2,4,4'-biphenyl triisocyanate, 2,4,4'-diphenylmethane triisocyanate, or the like can be used.
[0138] Isocyanate compounds having two or more isocyanate groups may also be used in the form of modified derivatives or polymers thereof. Herein, in order to effectively improve the elastic modulus of the cured region, MDI exhibiting high crystallinity, i.e., a symmetrical structure is preferred; in terms of processability, MDI comprising a modified body is more preferred, because MDI is liquid at room temperature.
[0139] <Production Method of Wiper Blade>
[0140] The production method of the wiper blade is not particularly limited and can be selected from known methods. For example, a polyurethane elastomer raw material composition can be injected into the cavity of a forming mold for the wiper blade, and then the composition can be cured by heating to obtain a lip having a tapered portion. The shape can be formed by cutting off the front end of the tapered portion. This is preferred because in this case, the first edge and the second edge can be formed with high smoothness. Alternatively, a pair of molded bodies in a series shape can be produced in a form in which the tapered portions are abutted while relative to each other, and then the molded bodies are cut in the length direction to produce each wiper blade. The blade support portion and the neck can be produced using conventionally known materials and production methods.
[0141] <Full process including wiper arm>
[0142] The wiper blade of the present disclosure may be used in various types of wiper systems such as tandem or opposing wiping types.
[0143] Example
[0144] The disclosure will be described below by way of manufacturing examples, embodiments and comparative examples, but the disclosure is not limited by these embodiments in any way. Except for those listed in the embodiments and comparative examples, reagents or industrial chemicals are used as raw materials. Unless otherwise stated, "parts" in the embodiments and comparative examples are all by mass.
[0145] Wiper blades were produced and evaluated in Examples and Comparative Examples. Tables 3 to 9 list the formulations and evaluation results of Examples and Comparative Examples.
[0146] [Example 1]
[0147] <Preparation of Raw Materials for Wiper Blades>
[0148] Herein, 352.6 g of 4,4′-diphenylmethane diisocyanate (trade name: Millionate MT, manufactured by Tosoh Corporation (hereinafter referred to as 4,4′-MDI and abbreviated as “MDI” in the table)), 10.0 g of triphenylmethane-4,4′,4″-triisocyanate (trade name: Ultite Super CA, manufactured by Toho Kasei Kogyo Co. Ltd.) as a trifunctional or higher polyfunctional isocyanate (hereinafter referred to as TTI) and 637.4 g of polybutylene adipate polyester polyol having a number average molecular weight of 2500 (trade name: Nippollan 3027, manufactured by Tosoh Corporation) (hereinafter referred to as PBA2500) were reacted at 80° C. for 3 hours to obtain a prepolymer having an NCO content of 10.0% by mass.
[0149] The components given in Table 1 below were then mixed to prepare a curing agent.
[0150] [Table 1]
[0151] Table 1
[0152]
[0153] The curing agent is added to the above-mentioned prepolymer and the whole is mixed to obtain a raw material composition. The raw material composition is injected into a forming mold for a wiper blade and cured at a temperature of 130° C. for 2 minutes. Then demolding is performed to obtain a polyurethane molded body. Herein, a release agent A is applied to the inside of the forming mold for a wiper blade in advance. The release agent A is a mixture of the materials described in Table 2 below.
[0154] [Table 2]
[0155] Table 2
[0156]
[0157] The wiper blade according to this embodiment was obtained by cutting the lip front end side of the obtained polyurethane molded body. The distances of the lip front end in the thickness direction and in the length direction were set to 0.6 mm and 450 mm, respectively. The obtained wiper blade was evaluated according to the following method.
[0158] [Measurement method of types and concentrations of polyfunctional alcohols]
[0159] The polyfunctional alcohols were detected by pyrolysis GC / MS (gas chromatography and mass spectrometry). The measurement conditions are listed below.
[0160] Sampling position: In each line segment drawn on the first conical surface and the second conical surface of the conical portion, parallel to the first edge and the second edge, at a distance of 0.5 mm from the first edge and the second edge, L' is used as the length of each line segment, and the sampling position is set at points P0', P1' and P2' which are 1 / 8L', 1 / 2L' and 7 / 8L' away from one end side of the line segment, respectively.
[0161] The samples collected at P0', P1' and P2' on the first tapered surface and the second tapered surface were measured by the following method: In the above sampling, a biocutter was used to cut out a member such as polyurethane.
[0162] Device:
[0163] - Pyrolyzer: Trade name: EGA / PY-3030D, manufactured by Frontier Laboratories Ltd.
[0164] - Gas chromatography apparatus: TRACE 1310 gas chromatograph, manufactured by Thermo Fisher Scientific Inc.
[0165] -Mass spectrometer: ISQLT, manufactured by Thermo Fisher Scientific Inc.
[0166] - Thermal decomposition temperature: 500℃
[0167] -GC column: stainless steel capillary column with inner diameter of 0.25 mm × 30 m
[0168] -Stationary phase: 5% phenyl dimethicone
[0169] - Heating conditions: Keep at 50°C for 3 minutes and increase the temperature to 300°C at 8°C / min
[0170] -MS conditions: mass range m / z 10~650
[0171] - Scanning speed: 1 second / scan
[0172] The polyfunctional alcohol species were characterized by means of GC / MS. A calibration curve was prepared by GC analysis of a qualitative polyfunctional alcohol substance of known concentration, and the substance was quantified based on the GC peak area ratio. The arithmetic mean of the values obtained for each sample at the first and second conical surfaces, at the above-mentioned P0', P1' and P2' was taken as the polyfunctional alcohol concentration of the first and second conical surfaces.
[0173] [Measurement of M1, M2 and M3]
[0174] Herein, M1 to M3 are measured by a direct sample introduction method (DI method) in which a sample is directly introduced into an ion source without passing through a gas chromatograph (GC).
[0175] The apparatus used herein was an ion trap type GC / MS (trade name: POLARIS Q, manufactured by ThermoFisherScientific Inc.) in which a direct exposure probe (DEP) was used as a direct introduction probe.
[0176] In each line segment drawn on the first tapered surface and the second tapered surface of the tapered portion, parallel to the first edge and the second edge, and at a distance of 0.5 mm from the first edge and the second edge, L' is used as the length of each line segment, and the sampling positions are set at points P0', P1', and P2' on the line segment that are 1 / 8L', 1 / 2L', and 7 / 8L' away from one end side, respectively.
[0177] The samples collected at the points P0', P1' and P2' on the first tapered surface and the second tapered surface are measured according to the following method: When sampling, a biocutter is used to cut out a member such as polyurethane.
[0178] About 0.1 μg of each sample sampled at each of the above P0', P1' and P2' of the first and second conical surfaces was fixed to the filament located at the front end of the probe, and the whole was directly inserted into the ionization chamber. It was then rapidly heated from room temperature to 1000°C at a constant heating rate (about 10°C / s), and the resulting vaporized gas was then detected using a mass spectrometer.
[0179] The sum of the integrated intensities of all peaks in the obtained total ion current thermogram is taken as the detected amount M1 of all ions.
[0180] In addition, (M2 / M1) is calculated using the values of M1 and M2 above, wherein M2 is the sum of the integrated intensities of the peaks in the extracted ion thermogram of the m / z values derived from trifunctional or higher polyfunctional isocyanates. In addition, (M3 / M1) is calculated using the values of M1 and M3, wherein M3 is the sum of the integrated intensities of the peaks in the extracted ion thermogram of the m / z values derived from diisocyanates. The arithmetic mean of the values obtained from each sample at P0', P1' and P2' of the first and second conical surfaces is taken as the values of (M2 / M1) and (M3 / M1) of the first and second conical surfaces, respectively.
[0181] In this example, TTI used as a trifunctional or higher polyfunctional isocyanate has a structure represented by the following chemical formula (3). In the extracted ion thermogram obtained in this evaluation, a peak derived from a cationized product of TTI having a peak top at a position of m / z 366.5 to 367.5 was detected. Therefore, in this example, the integrated intensity of this peak was taken as M2.
[0182]
[0183] In another example described later, for an elastic part made of a polyurethane synthesized using polymerized MDI as a trifunctional or higher polyfunctional isocyanate, a peak derived from a cationized polymerized MDI having a structure represented by chemical formula (1)' was detected in the extracted ion thermogram obtained in this evaluation, and the peak had peak tops at positions in which the m / z value representing n = 1 was in the range of 380.5 to 381.5, the m / z value representing n = 2 was in the range of 511.5 to 512.5, the m / z value representing n = 3 was in the range of 642.5 to 643.5, and the m / z value representing n = 4 was in the range of 773.5 to 774.5. Therefore, in this example, the sum of the integrated intensities of the peaks was taken as M2.
[0184] Similarly, tri(phenylisocyanate) (TPTI) thiophosphate used as a trifunctional or higher polyfunctional isocyanate in the examples described later has a structure represented by chemical formula (4). In the extracted ion thermogram obtained in this evaluation, a peak derived from a cationized product of TPTI having a peak top at a position of m / z of 464.5 to 465.5 was detected. Therefore, in this example, the integrated intensity of this peak was taken as M2.
[0185]
[0186] In contrast, in the case of 4,4'-MDI as diisocyanate, in the range of m / z of the structure represented by the chemical formula (2) derived from 4,4'-MDI of 249.5 to 250.5, the structure represented by the above chemical formula (2) is cationized and detected. The integrated intensity of the peak of the extracted ion thermogram corresponding to the structure is taken as (M3).
[0187] [Measurement method of elastic modulus]
[0188] The elastic modulus by means of a scanning probe microscope (SPM) (trade name: MFP-3D Origin, manufactured by Oxford Instruments plc) was measured according to the following method.
[0189] First, the samples were prepared as follows. For each of the obtained wiper blades, Figure 3 As shown in FIG. 1 , a first tapered surface and a first edge formed on the front end surface are set, and when a first line segment of length L1 is drawn in parallel with the first edge and at a distance of 10 μm from the first edge, three 2 mm long lines are cut out with points P0, P1, and P2 on the line segment at 1 / 8L1, 1 / 2L1, and 7 / 8L1 from one end as the center of gravity and one side parallel to the first line segment. 2 A square measurement sample of 100 μm was cut from each measurement sample at -50°C using a cryo-microtome (UC-6 (product name), manufactured by Leica Microsystems GmbH) to obtain a 1 μm thick polyurethane sheet with P0, P1 and P2 as the center of gravity and one side parallel to the first line segment. Three measurement samples were prepared in this way. Each of the obtained measurement samples was placed on a smooth silicon wafer and allowed to stand for 24 hours at a room temperature of 25°C and a humidity of 50%.
[0190] Next, the silicon wafer with the measurement sample on it was placed on the SPM stage, and SPM observation was performed. The spring constant and proportional constant of the silicon cantilever (trade name: OMCL-AC160, manufactured by Olympus Corporation, tip curvature radius: 8 nm) were confirmed in advance according to the thermal noise method of the SPM device as follows (spring constant: 30.22 nN / nm, proportional constant: 82.59 nm / V).
[0191] The cantilever was pre-tuned and the resonant frequencies of the cantilever were found (285 KHz (first order) and 1.60 MHz (higher order)).
[0192] The measurement mode of SPM was AM-FM mode, the free amplitude of the cantilever was set to 3 V, the set point amplitude was set to 2 V (first order) and 25 mV (higher order), and the phase image was obtained by scanning at a scanning speed of 1 Hz and a scanning point number of 256 in the vertical direction and 256 in the horizontal direction in a field of view of 70 μm×70 μm in size. The field of view position was selected so that P0, P1 and P2 of each measurement sample existed in the center of the field of view and one side of the field of view was parallel to the first line segment.
[0193] Based on the obtained phase image, the site of each measurement sample where the elastic modulus is to be measured by the force curve is specified. Specifically, Figure 4 and Figure 5 As shown in the figure, within the 70μm×70μm phase image, the measurement site is designated as the position of 70,000 points with a spacing (interval) of 0.1μm in the longitudinal and lateral directions in an area corresponding to a rectangle with points P0, P1 and P2 as the center and having sides of 70μm parallel to the first line segment and sides of 10μm perpendicular to the first line segment.
[0194] Thereafter, for all points, a force curve measurement in contact mode is performed for each point. The force curve is obtained under the following conditions. In the force curve measurement, the piezoelectric element as the driving source of the cantilever is controlled so that the front end of the cantilever turns back once the deflection caused by contact with the sample surface reaches a constant value. The turning point at this time is called the trigger value, which indicates the specific degree to which the voltage increases from the deflection voltage at the beginning of the force curve when the cantilever turns back. In this measurement, the force curve is measured with the trigger value set to 0.2V. As other force curve measurement conditions, the distance from the front end position of the cantilever in the standby state to the cantilever turning back at the trigger value is set to 500nm, and the scanning speed (the speed at which the probe reciprocates once) is set to 1Hz. Thereafter, the obtained force curves are fitted one by one based on the Hertz theory to calculate the elastic modulus. The elastic modulus (Young's modulus) according to the Hertz theory is calculated according to the following calculation formula (*1).
[0195] Calculation formula (*1)
[0196] F=(4 / 3)E*R 1 / 2 d 3 / 2
[0197] Herein, F represents the force applied by the cantilever on the sample at the time point when the cantilever turns back, E* is the complex elastic modulus, R is the radius of curvature of the front end of the cantilever (8 nm), and d is the deformation of the sample at the time point when the cantilever turns back.
[0198] In addition, d is calculated by the following calculation formula (*2).
[0199] Calculation formula (*2)
[0200] d = Δz-D.
[0201] Here, Δz is the displacement of the piezoelectric element from the time when the tip of the cantilever contacts the sample until the tip turns back, and D is the warping amount of the cantilever at the time when the cantilever turns back. In addition, D is calculated based on the following calculation formula (*3).
[0202] Calculation formula (*3)
[0203] D = α·ΔV deflection
[0204] In the calculation formula (*3), α is the proportionality constant (involute constant) of the cantilever, and ΔVdeflection is the change in deflection voltage from the time the cantilever starts to contact the sample until the cantilever turns back.
[0205] In addition, F is calculated based on the following calculation formula (*4).
[0206] Calculation formula (*4)
[0207] F=κ·D
[0208] Where κ is the spring constant of the cantilever.
[0209] Here, ΔV deflection and Δz are measured values, so E* in calculation formula (*1) is obtained based on calculation formulas (*1) to (*4). The elastic modulus (Young's modulus) Es to be obtained is calculated based on the following calculation formula (*5).
[0210] Calculation formula (*5)
[0211] 1 / E * =[(1-Vs 2 ) / Es]-[(1-Vi 2 ) / Ei]
[0212] Vs: Poisson's ratio of the sample (fixed at 0.33 in this example);
[0213] Vi: Poisson's ratio of the cantilever tip (the value of silicon is used in this embodiment);
[0214] Ei: Young's modulus of the cantilever tip (in this embodiment, the value of silicon is used).
[0215] The elastic modulus was measured at 70,000 points in the longitudinal direction and in the transverse direction at a pitch (interval) of 0.1 μm in a rectangular observation area (three 10 μm×70 μm observation areas) with each point P0, P1, and P2 as the center of gravity and having a side of 70 μm in length parallel to the first line segment and a side of 10 μm in length perpendicularly intersecting the first line segment. Then, the average value of the elastic modulus values calculated from the force curve at a total of 210,000 points was taken as the elastic modulus of the first tapered surface.
[0216] The standard deviation was calculated from the elastic modulus values at a total of 210,000 points. The coefficient of variation of the elastic modulus of the first tapered surface was calculated based on the following formula 1 from the average value and the standard deviation of the elastic modulus values.
[0217] Formula (1): Coefficient of variation (%) = standard deviation / average value of elastic modulus value × 100
[0218] The average value of the elastic modulus value of the second tapered surface and the coefficient of variation of the elastic modulus of the second tapered surface were calculated in the same manner as described above.
[0219] <Evaluation of wiping performance>
[0220] The wiping property of the wiper blade was evaluated using a test device for wiping performance test described in Japanese Industrial Standard (JIS) D5710:1998 (Automobile Parts-Wiper Arm and Wiper Blade). In this test, the wiper blade was installed and silicone oil (trade name: KF-96-50cs, manufactured by Shin-Etsu Chemical Co., Ltd.) was applied to the entire wiping surface in a state simulating an oil film on a glass surface as a member to be cleaned, and then cleaning was performed under the following conditions.
[0221] After the wiper blade has been moved back and forth once, the residual state on the glass surface is observed from the back side of the cleaning surface, and the uneven gloss and the effect on the visual field are visually confirmed. The result is calculated as the ratio of the area of the portion where the silicone oil film is removed to the area of the surface wiped by the wiper blade (hereinafter referred to as the silicone oil film removal area ratio (%)).
[0222] The wiping performance was evaluated according to the following criteria based on the calculated oil film removal area ratio. These results were taken as the initial wiping performance. In addition, the wiper blade was reciprocated under the following durability conditions, and after the reciprocating number of times was 100,000 and 500,000, the wiping performance after durability was confirmed in the same manner as the evaluation of the initial wiping performance. Table 3 lists the results of the initial evaluation and the evaluation after durability as the wiping performance of the wiper blade.
[0223] [Wipe conditions]
[0224] Load applied to wiper blade: 10N / m
[0225] Wiping reciprocating speed of the wiper blade: 50 times / min
[0226] [Durability conditions]
[0227] Water coating amount: 100~500mL / min
[0228] Load applied to wiper blade: 18N / m
[0229] Wiping reciprocating speed of the wiper blade: 50 times / min
[0230] [Evaluation criteria]
[0231] Grade A: Silicone oil film removal area rate is more than 95%
[0232] Grade B: Silicone oil film removal area ratio is 90% or more and less than 95%
[0233] Grade C: Silicone oil film removal area ratio is 85% or more and less than 90%
[0234] Grade D: Silicone oil film removal area ratio is 80% or more and less than 85%
[0235] Grade E: Silicone oil film removal area rate is less than 50%
[0236] [Examples 2 to 10]
[0237] A wiper blade was produced and evaluated in the same manner as in Example 1, except that the kinds and usage amounts of various materials for the prepolymer and the kinds and usage amounts of various materials for the curing agent were as described in Table 3.
[0238] In Example 3, tris(phenyl isocyanate)phosphorothioate (trade name: Ultite SuperCAII, manufactured by Toho Kasei Kogyo Co., Ltd.) (hereinafter referred to as TPTI) was used as a tri- or higher-functional isocyanate for a prepolymer.
[0239] In Example 5, polymeric MDI (trade name: Millionate MR-400, manufactured by Tosoh Corporation) (hereinafter referred to as MR400) was used as a trifunctional or higher polyfunctional isocyanate for a prepolymer.
[0240] In Example 6, glycerin (Tokyo Chemical Industry Co., Ltd.) was used as a polyfunctional alcohol for a curing agent.
[0241] [Examples 11 to 20]
[0242] A wiper blade was produced and evaluated in the same manner as in Example 1, except that the kinds and usage amounts of various materials for the prepolymer and the kinds and usage amounts of various materials for the curing agent were as described in Table 4.
[0243] In Example 13, trimethylolpropane (manufactured by Tokyo Chemical Industry Co., Ltd.) (hereinafter referred to as TMP) was used as a polyfunctional alcohol for a curing agent.
[0244] In Example 14, polymeric MDI (trade name: Millionate MR-200, manufactured by Tosoh Corporation) (hereinafter referred to as MR200) was used as a polyfunctional isocyanate for a prepolymer.
[0245] In Example 18, polybutylene adipate polyester polyol (trade name: Nippollan 4009, manufactured by Tosoh Corporation) (hereinafter referred to as PBA1000) was used as a polyol for a curing agent.
[0246] In Example 19, polyhexamethylene adipate polyester polyol (trade name: Nippollan 136, manufactured by Tosoh Corporation) having a number average molecular weight of 2600 (hereinafter referred to as PHA2600) was used as a polyol for a prepolymer.
[0247] [Examples 21 to 28]
[0248] A wiper blade was produced and evaluated in the same manner as in Example 1, except that the kinds and usage amounts of various materials for the prepolymer and the kinds and usage amounts of various materials for the curing agent were as described in Table 5.
[0249] [Example 29]
[0250] Herein, 304.0 g of 4,4′-MDI, 20.0 g of polymeric MDI (trade name: Cosmonate M-200, manufactured by Mitsui Chemicals, Inc.) (hereinafter referred to as M200) and 676.0 g of polytetramethylene ether glycol having a number average molecular weight of 2000 (trade name: PTG-2000SN, manufactured by Hodogaya Chemical Co., Ltd.) (hereinafter referred to as PTG2000SN) were reacted at 80° C. for 3 hours to prepare a prepolymer having an NCO content of 7.9% by mass.
[0251] Furthermore, 39.6 g of pentaerythritol, 290.3 g of polytetramethylene ether glycol having a number average molecular weight of 1000 (trade name: PTG-1000SN, manufactured by Hodogaya Chemical Co., Ltd.) (hereinafter referred to as PTG1000SN), 0.13 g of Polycat 46 and 0.55 g of No. 25 were mixed to produce a curing agent.
[0252] Then, a raw material composition was obtained by mixing the prepolymer prepared above and a curing agent. The raw material composition was injected into a forming mold for a wiper blade and cured at a temperature of 130° C. for 6 minutes. Then demolding was performed to obtain a polyurethane molded body. The obtained polyurethane molded body was processed in the same manner as in Example 1 to produce a wiper blade, which was then evaluated.
[0253] [Examples 30 to 32]
[0254] A wiper blade was produced and evaluated in the same manner as in Example 1, except that the kinds and usage amounts of various materials for the prepolymer and the kinds and usage amounts of various materials for the curing agent were as shown in Tables 5 to 6.
[0255] [Example 33]
[0256] Herein, 349.5 g of 4,4′-MDI and 650.5 g of polybutylene adipate polyester polyol having a number average molecular weight of 2000 (trade name: Nippollan 4010, manufactured by Tosoh Corporation) (hereinafter referred to as PBA2000) were reacted at 80° C. for 3 hours without adding a trifunctional or higher polyfunctional isocyanate to prepare a prepolymer having an NCO content of 9.0% by mass.
[0257] A curing agent was produced by mixing 40.4 g of 1,4-BD, 5.0 g of glycerol, 5.0 g of PHA1000, 0.05 g of Polycat 46 and 0.25 g of No. 25. The curing agent was mixed with a prepolymer prepared in advance to obtain a raw material composition. The raw material composition was injected into a forming mold for a wiper blade and cured at a temperature of 130° C. for 10 minutes. Then demolding and secondary curing was performed at a temperature of 130° C. for 60 minutes to obtain a polyurethane molded body. The obtained polyurethane molded body was processed in the same manner as in Example 1 to produce a wiper blade, which was then evaluated.
[0258] [Example 34]
[0259] A wiper blade was produced in the same manner as in Example 1 except that the kinds and amounts of various materials for the prepolymer and the kinds and amounts of various materials for the curing agent were as shown in Table 6. Next, the lip portion of the wiper blade was irradiated with ultraviolet rays so that the accumulated light amount of ultraviolet rays was 492 mJ / cm 2 , to obtain the wiper blade according to the present embodiment. A low-pressure mercury ozone-free lamp (manufactured by Toshiba Lighting & Technology Corporation) having a maximum emission wavelength peak at a wavelength of 254 nm was used as a light source for ultraviolet rays. The wiper blade was evaluated in the same manner as in Example 1.
[0260] [Examples 35 and 36]
[0261] A wiper blade was produced in the same manner as in Example 1, except that the kinds and usage amounts of various materials for the prepolymer and the kinds and usage amounts of various materials for the curing agent were as shown in Table 6. Then, wiper blades according to Examples 35 and 36 were obtained by irradiating the obtained wiper blade with ultraviolet rays in the same manner as in Example 34, except that the accumulated light amount was changed to the values shown in Table 6. These wiper blades were evaluated in the same manner as in Example 1.
[0262] [Example 37]
[0263] Here, 296.6 g of 4,4′-MDI and 703.4 g of PBA2000 were reacted at 80° C. for 3 hours without adding trifunctional or higher polyfunctional isocyanate to obtain a prepolymer having an NCO content of 7.0% by mass.
[0264] Without adding PHA1000, a curing agent is produced by mixing 52.0g 1,4-BD, 19.2g glycerol, 0.05g Polycat 46 and 0.25g No.25. The curing agent is mixed with a prepolymer prepared in advance to obtain a raw material composition. The raw material composition is injected into a forming mold for a wiper blade and cured at a temperature of 130°C for 10 minutes. Then demolding and secondary curing is performed at a temperature of 130°C for 60 minutes to obtain a polyurethane molded body. The obtained polyurethane molded body is processed in the same manner as in Example 1 to produce a wiper blade, which is then evaluated. The wiper blade is irradiated with ultraviolet rays in the same manner as in Example 34 to obtain a wiper blade according to this embodiment. Ultraviolet irradiation is performed so that the cumulative light amount is 1968mJ / cm 2 The obtained wiper blade was evaluated in the same manner as in Example 1.
[0265] [Example 38]
[0266] A wiper blade was produced and evaluated in the same manner as in Example 1, except that the kinds and usage amounts of various materials for the prepolymer and the kinds and usage amounts of various materials for the curing agent were as shown in Table 6.
[0267] [Examples 39 and 40]
[0268] A wiper blade was produced in the same manner as in Example 1, except that the kinds and usage amounts of various materials for the prepolymer and the kinds and usage amounts of various materials for the curing agent were as shown in Table 6. Then, wiper blades according to Examples 39 and 40 were obtained by irradiating the obtained wiper blade with ultraviolet rays in the same manner as in Example 34, except that the accumulated light amount was changed to the values shown in Table 6. These wiper blades were evaluated in the same manner as in Example 1.
[0269] [Example 41]
[0270] The kinds and usage amounts of various materials used for the prepolymer are shown in Table 7. These materials were mixed and reacted at a temperature of 80° C. for 3 hours to prepare a prepolymer having an NCO content of 9.0% by mass.
[0271] Various materials for curing agent as shown in Table 7 are mixed in the amounts shown in Table 7 to prepare a curing agent. Then, a raw material composition is obtained by mixing the above prepolymer and the curing agent. The raw material composition is injected into a forming mold for a wiper blade and cured at a temperature of 130° C. for 10 minutes. Then demolding and secondary curing is performed at a temperature of 130° C. for 60 minutes to obtain a polyurethane molded body. The obtained polyurethane molded body is processed in the same manner as in Example 1 to produce a wiper blade according to this embodiment. The obtained wiper blade is evaluated in the same manner as in Example 1.
[0272] [Examples 42 to 44]
[0273] Prepolymers were prepared in the same manner as in Example 41, except that the kinds and amounts of various materials used for the prepolymers were as shown in Table 7. The NCO content of the prepolymer of Example 42 was 8.2% by mass, the NCO content of the prepolymer of Example 43 was 15.0% by mass, and the NCO content of the prepolymer of Example 44 was 18.0% by mass.
[0274] The curing agent was prepared in the same manner as in Example 41, except that various materials for the curing agent and the amounts used thereof were as shown in Table 7. A wiper blade was produced and evaluated in the same manner as in Example 41, except that these prepolymers and the curing agent were used.
[0275] [Examples 45 and 46]
[0276] The wiper blade obtained in Example 44 was irradiated with ultraviolet rays in the same manner as in Example 34, except that the accumulated light amount was set to the value described in Table 6, to obtain wiper blades according to Examples 45 and 46. The obtained wiper blades were evaluated in the same manner as in Example 1.
[0277] [Examples 47 to 50]
[0278] Prepolymers were prepared in the same manner as in Example 41, except that the kinds and amounts of various materials used for the prepolymers were as shown in Table 7. The NCO content of the prepolymer according to Example 47 was 10.0% by mass, the NCO content of the prepolymer according to Example 48 was 9.6% by mass, the NCO content of the prepolymer according to Example 49 was 9.3% by mass, and the NCO content of the prepolymer according to Example 50 was 9.2% by mass.
[0279] The curing agent was prepared in the same manner as in Example 41, except that various materials for the curing agent and the amounts used thereof were as shown in Table 7. Wiper blades according to Examples 47 to 50 were produced and evaluated in the same manner as in Example 41, except that the above-mentioned prepolymer and curing agent were used.
[0280] [Example 51]
[0281] Herein, the front end 2 mm of the lip of the wiper blade produced in the same manner as in Example 37 was immersed in 4,4'-MDI dissolved at a temperature of 80°C for 1 minute. Thereafter, 4,4'-MDI attached to the surface of the immersed portion of the wiper blade was wiped off using a sponge soaked in butyl acetate. The wiper blade was then aged for 24 hours under an environment of a temperature of 23°C and a relative humidity of 50% to form a cured area at the front end of the lip. Thus, the wiper blade according to the present example was obtained. The wiper blade was evaluated in the same manner as in Example 1.
[0282] [Example 52]
[0283] A wiper blade according to this example was produced in the same manner as in Example 51 except that heating was performed at 100° C. for 30 minutes after wiping off 4,4′-MDI attached to the surface of the impregnated wiper blade.
[0284] [Example 53]
[0285] The wiper blade according to this example was obtained by subjecting the wiper blade produced in the same manner as in Example 4 to the same surface treatment as in Example 51, except that the immersion time in 4,4'-MDI was set to 3 minutes. The wiper blade was evaluated in the same manner as in Example 1.
[0286] [Example 54]
[0287] A wiper blade according to this example was produced in the same manner as in Example 53 except that heating was performed at 100° C. for 30 minutes after wiping off 4,4′-MDI attached to the surface of the impregnated wiper blade.
[0288] Comparative Example 1
[0289] Table 9 shows the types and usage amounts of various materials used for prepolymers. These materials are mixed and reacted at a temperature of 80°C for 3 hours to prepare a prepolymer having an NCO content of 14.0% by mass. Various materials for curing agents as shown in Table 9 are mixed in the amounts shown in Table 9 to prepare curing agents. Then, a raw material composition is obtained by mixing the above prepolymer and curing agent. The raw material composition is injected into a forming mold for a wiper blade and cured at a temperature of 130°C for 10 minutes. Then demolding and secondary curing is performed at a temperature of 130°C for 60 minutes to obtain a polyurethane molded body. The obtained polyurethane molded body is processed in the same manner as in Example 1 to produce a wiper blade according to this embodiment. The obtained wiper blade is evaluated in the same manner as in Example 1.
[0290] [Comparative Example 2]
[0291] A prepolymer having an NCO content of 9.0% by mass was prepared in the same manner as in Comparative Example 1, except that the kinds and amounts of various materials used for the prepolymer were as shown in Table 9. A curing agent was prepared in the same manner as in Comparative Example 1, except that various materials and amounts of various materials used for the curing agent were as shown in Table 9. A wiper blade according to this Comparative Example was produced and evaluated in the same manner as in Comparative Example 1, except that the above-mentioned prepolymer and curing agent were used.
[0292] [Comparative Example 3]
[0293] A prepolymer having an NCO content of 7.0% by mass was prepared in the same manner as in Comparative Example 1, except that the types and amounts of various materials used for the prepolymer were as shown in Table 9. A curing agent was prepared in the same manner as in Comparative Example 1, except that various materials used for the curing agent and the amounts thereof were as shown in Table 9. A wiper blade was produced in the same manner as in Comparative Example 1, except that the above-mentioned prepolymer and curing agent were used. The accumulated light amount was set to 8200 mJ / cm 2 Except for this, a wiper blade according to the present comparative example was obtained by irradiating the obtained wiper blade with ultraviolet rays in the same manner as in Example 34. The obtained wiper blade was evaluated in the same manner as in Example 1.
[0294] [Comparative Example 4]
[0295] To 100 parts by mass of natural rubber, 48.0 parts by mass of carbon black (trade name: Toka Black #7360SB, manufactured by Tokai Carbon Co., Ltd.), 5.0 parts by mass of zinc oxide (trade name: Zinc White 2, manufactured by Sakai Chemical Industry Co., Ltd.), 1.0 parts by mass of zinc stearate (trade name: SZ-2000, manufactured by Sakai Chemical Industry Co., Ltd.) and 20 parts by mass of calcium carbonate (trade name: Nanox #30, manufactured by Maruo Calcium Co., Ltd.) were added, and the whole was kneaded for 15 minutes in a sealed mixer adjusted to 50° C. To the resulting mixture, 1.2 parts by mass of sulfur and 4.5 parts by mass of tetrabenzylthiuram sulfide (TBzTD) (trade name: Perkacit TBzTD, manufactured by FlexSys, Inc.) were further added as a vulcanizing agent. The obtained product was kneaded for 10 minutes using a two-roll mill cooled to a temperature of 25° C. to obtain a rubber composition. The obtained rubber composition was placed in a forming mold for a wiper blade and vulcanized by heating at a temperature of 170° C. for 20 minutes. Then demolding was performed to obtain a wiper blade according to this comparative example. The obtained wiper blade was evaluated in the same manner as in Example 1.
[0296] Tables 3 to 9 show the evaluation results of the wiper blades according to the respective Examples and Comparative Examples.
[0297] [Table 3]
[0298]
[0299] [Table 4]
[0300]
[0301] [Table 5]
[0302]
[0303] [Table 6]
[0304]
[0305] [Table 7]
[0306]
[0307] [Table 8] Table 8
[0308]
[0309] [Table 9]
[0310] Table 9
[0311]
[0312] The present disclosure is not limited to the above embodiments, and various modifications and changes may be made without departing from the spirit and scope of the present disclosure. Therefore, the claims are attached herewith to disclose the scope of the present disclosure.
[0313] This application claims priority based on Japanese Patent Application No. 2020-130825 filed on July 31, 2020, Japanese Patent Application No. 2021-077293 filed on April 30, 2021, and Japanese Patent Application No. 2021-106577 filed on June 28, 2021, the entire contents of which are incorporated herein.
[0314] Description of Reference Numerals
[0315] 1. Blade support
[0316] 2 Neck
[0317] 3. Lips
[0318] 4 Conical part
[0319] 5First conical surface
[0320] 6 Second conical surface
[0321] 7Front end
[0322] 8 First Edge
[0323] 9 The Second Edge
[0324] 10 Cleaned components
[0325] 11The first line segment
[0326] 12Observation Area
Claims
1. A vehicle wiper blade for a wiper device for a vehicle windshield, characterized in that: It includes: A scraper blade supporting portion; and a lip pivotably connected to the blade support via a neck; The lip has a tapered portion in which, in a cross section along a direction perpendicular to the length direction of the wiper blade, the width of the lip gradually decreases from a side close to the blade support portion toward a direction farthest from the blade support portion; The lip has a first tapered surface and a second tapered surface constituting the tapered portion; and a front end surface, the front end surface, together with the first tapered surface and the second tapered surface, forming a first edge and a second edge on a side of the lip portion that is farthest from the blade support portion; It is assumed that a first line segment is drawn on the first conical surface, parallel to the first edge and at a distance of 10 μm from the first edge; Define the length of the first line segment as L1; Points on the first line segment that are (1 / 8)L1, (1 / 2)L1, and (7 / 8)L1 away from one end are defined as P0, P1, and P2, respectively; and When the elastic modulus of the first tapered surface is measured at 70,000 points at a pitch of 0.1 μm in each of three rectangular observation areas, each of which has a point P0, P1, and P2 as a center of gravity and has a side of 70 μm in length parallel to the first line segment and a side of 10 μm in length perpendicularly intersecting the first line segment, using a scanning probe microscope, The average value of the 210,000 elastic modulus values obtained is 15 MPa to 470 MPa, and the coefficient of variation of the elastic modulus is 17.6% or less; and Assume that a second line segment is drawn on the second tapered surface, parallel to the second edge and at a distance of 10 μm from the second edge; Define the length of the second line segment as L2; Points on the second line segment that are (1 / 8)L2, (1 / 2)L2, and (7 / 8)L2 away from one end are defined as P3, P4, and P5, respectively; When the elastic modulus of the second tapered surface is measured at 70,000 points at a pitch of 0.1 μm in each of three rectangular observation areas, each of which has points P3, P4, and P5 as a center of gravity and has a side of 70 μm in length parallel to the second line segment and a side of 10 μm in length perpendicularly intersecting the second line segment, using a scanning probe microscope, The average value of the 210,000 elastic modulus values obtained was 15 MPa to 470 MPa, and the coefficient of variation of the elastic modulus was less than 17.6%; The tapered portion comprises polyurethane; The polyurethane comprises a reaction product of a raw material composition, wherein the raw material composition comprises an isocyanate compound containing a trifunctional or higher-functional polyfunctional isocyanate; and The isocyanate compound further comprises a diisocyanate; and It is assumed On the first tapered surface and the second tapered surface of the tapered portion, line segments are drawn in parallel with the first edge and the second edge at a distance of 0.5 mm from the first edge and the second edge, respectively; The length of each line segment is defined as L', The points on each of the line segments that are 1 / 8L', 1 / 2L', and 7 / 8L' away from one end are defined as P0', P1', and P2', respectively; and When the samples collected at P0', P1' and P2' on the first and second conical surfaces are heated to 1000°C at a heating rate of 10°C / s by using a direct sample introduction type mass spectrometer that heats and vaporizes each of the samples in an ionization chamber and ionizes the molecules of each of the samples, the obtained The detected amount of all ions is defined as M1, The integrated intensity of the peak in the extracted ion thermogram corresponding to the range of m / z values derived from the trifunctional or higher polyfunctional isocyanate is defined as M2; and The integrated intensity of the peak in the extracted ion thermogram corresponding to the range of m / z values derived from the diisocyanate is defined as M3; On the first tapered surface, M2 / M1 is 0.0010 to 0.0150, and M3 / M1 is 0.0200 to 0.1100; and On the second tapered surface, M2 / M1 is 0.0010 to 0.0150, and M3 / M1 is 0.0200 to 0.1100.
2. The vehicle wiper blade according to claim 1, The raw material composition further comprises: Alcohols including trifunctional or higher polyfunctional alcohols. 3 . The vehicle wiper blade according to claim 2 , wherein the alcohol further contains glycol.
4. The vehicle wiper blade according to claim 2 or 3, It is assumed that line segments are drawn on the first tapered surface and the second tapered surface of the tapered portion, parallel to the first edge and the second edge, at a distance of 0.5 mm from the first edge and the second edge, respectively. The length of each of the line segments is defined as L', and The points on each of the line segments that are 1 / 8L', 1 / 2L', and 7 / 8L' away from one end are defined as P0', P1', and P2', respectively; and When the samples collected at P0', P1' and P2' on the first and second conical surfaces are measured by pyrolysis GC / MS, On the first tapered surface, the concentration of trifunctional or higher polyfunctional alcohol in the polyurethane is 0.04 mmol / g to 0.39 mmol / g; and On the second tapered surface, the concentration of the trifunctional or higher-functional polyfunctional alcohol in the polyurethane is 0.04 mmol / g to 0.39 mmol / g. 5 . The vehicle wiper blade according to claim 2 , wherein the trifunctional or higher polyfunctional alcohol contains at least one selected from the group consisting of trimethylolpropane and glycerin. The vehicle wiper blade according to any one of claims 1 to 3, wherein the trifunctional or higher polyfunctional isocyanate is at least one selected from the group consisting of triphenylmethane-4,4',4"-triisocyanate TTI, thiophosphoric acid tris(phenylisocyanate) TPTI and polymeric MDI.
7. The vehicle wiper blade according to any one of claims 1 to 3, in, In the measurement of the elastic modulus on the first conical surface, The average value of the elastic modulus is greater than or equal to 32 MPa and less than or equal to 62 MPa; and In the measurement of the elastic modulus on the second conical surface, The average value of the elastic modulus value is 32 MPa or more and 62 MPa or less.
8. The vehicle wiper blade according to any one of claims 1 to 3, in, In the measurement of the elastic modulus on the first conical surface, The coefficient of variation of the elastic modulus is 6.0% or less; and In the measurement of the elastic modulus on the second conical surface, The coefficient of variation of the elastic modulus is 6.0% or less.
Citation Information
Patent Citations
Wiper rubber for window wiper wiper blades
JP2011518713A
Game machine
JP2020130825A
Computer program and information processing method
JP2021077293A
Beer-like foamable beverage
JP2021106577A
Design method for wiper blade, and wiper blade
JP2004243917A